2014
DOI: 10.2169/internalmedicine.53.2624
|View full text |Cite
|
Sign up to set email alerts
|

Oral Tacrolimus for Megacolon in Patients with Severe Ulcerative Colitis

Abstract: Toxic megacolon is an infrequent but life-threatening complication that occurs most commonly in patients with severe ulcerative colitis. Intravenous steroids are often recommended for patients with toxic megacolon secondary to ulcerative colitis. However, steroid dependency may mask the presence of intra-abdominal sepsis and is associated with refractoriness, during which cytomegalovirus reactivation may occur. In this report, we present two rare cases of megacolon accompanying pancolonic severe ulcerative col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Based on the results of this study, we believe that starting with oral tacrolimus may be a useful strategy for patients with severe or refractory UC. ( 27 , 28 )…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this study, we believe that starting with oral tacrolimus may be a useful strategy for patients with severe or refractory UC. ( 27 , 28 )…”
Section: Discussionmentioning
confidence: 99%
“…In adults, long rectal tube insertion combined with intermittent rolling maneuvers (169) and the knee‐elbow position (170) have been used to promote decompression. Case reports indicate potential effectiveness of infliximab (171–173), leukocytapheresis (174), tacrolimus (175,176), or hyperbaric oxygen (177) for treating toxic megacolon, but the evidence is anecdotal. Although CMV infection is more commonly associated with toxic megacolon, there is not enough evidence to support empiric treatment with ganciclovir without confirmation of CMV infection (178).…”
Section: Initial Managementmentioning
confidence: 99%
“…Our results showed that all CMV-DNA-positive patients who were treated with oral tacrolimus without ganciclovir showed clinical responses and decreased numbers of CMV-DNA copies (Figure 3). Because the use of steroids is known to increase the risk of CMV infection, which is associated with disease exacerbation and refractoriness, oral tacrolimus should be used prior to steroid therapy in patients with severe or refractory UC [57].…”
Section: Impact Of Tacrolimus On Cytomegalovirus (Cmv) Colitismentioning
confidence: 99%